ORMDL2 Deficiency Potentiates the ORMDL3-Dependent Changes in Mast Cell Signaling - Bugajev, Viktor; Halova, Ivana; Demkova, Livia; Cernohouzova, Sara; Vavrova, Petra; Mrkacek, Michal; Utekal, Pavol; Draberova, Lubica; Kuchar, Ladislav; Schuster, Björn; Draber, Petr (Frontiers in Immunology, 2021)
The systemic anaphylactic reaction is a life-threatening allergic response initiated by activated mast cells. Sphingolipids are an essential player in the development and attenuation of this response. De novo synthesis of sphingolipids in mammalian cells is inhibited by the family of three ORMDL proteins (ORMDL1, 2, and 3). However, the cell and tissue-specific functions of ORMDL proteins in mast cell signaling are poorly understood. This study aimed to determine cross-talk of ORMDL2 and ORMDL3 proteins in IgE-mediated responses. To this end, we prepared mice with whole-body knockout (KO) of Ormdl2 and/or Ormdl3 genes and studied their role in mast cell-dependent activation events in vitro and in vivo. We found that the absence of ORMDL3 in bone marrow-derived mast cells (BMMCs) increased the levels of cellular sphingolipids. Such an increase was further raised by simultaneous ORMDL2 deficiency, which alone had no effect on sphingolipid levels. Cells with double ORMDL2 and ORMDL3 KO exhibited increased intracellular levels of sphingosine-1-phosphate (S1P). Furthermore, we found that concurrent ORMDL2 and ORMDL3 deficiency increased IκB-α phosphorylation, degranulation, and production of IL-4, IL-6, and TNF-α cytokines in antigen-activated mast cells. Interestingly, the chemotaxis towards antigen was increased in all mutant cell types analyzed. Experiments in vivo showed that passive cutaneous anaphylaxis (PCA), which is initiated by mast cell activation, was increased only in ORMDL2, 3 double KO mice, supporting our in vitro observations with mast cells. On the other hand, ORMDL3 KO and ORMDL2, 3 double KO mice showed faster recovery from passive systemic anaphylaxis, which could be mediated by increased levels of blood S1P presented in such mice. Our findings demonstrate that Ormdl2 deficiency potentiates the ORMDL3-dependent changes in mast cell signaling.